Effects of the Addition of Microbial Agents After Dazomet Fumigation on the Microbial Community Structure in Soils with Continuous Cropping of Strawberry (Fragaria × Ananassa Duch.) - Ran Wu; Yan Li; Jian Meng; Jiangwei Han (Microorganisms)
To study the effects of different microbial agents on the microbial community structure of continuously cropped strawberry soil after soil fumigation, seven treatments were applied: T1 (Trichoderma harzianum + Bacillus subtilis + actinomycetes), T2 (Trichoderma harzianum + Bacillus subtilis), T3 (Trichoderma harzianum + actinomycetes), T4 (CK) (water control), T5 (Bacillus subtilis), T6 (actinomycetes) and T7 (Trichoderma harzianum). A high-throughput sequencing platform (Illumina HiSeq 2500) was used to analyze the soil bacterial and fungal communities and their compositions. Compared with the T4 (CK) treatment, the application of microbial agents increased the richness and diversity of soil bacteria and fungi, and the effects of single microbial agents and compound microbial agents differed. The richness, diversity indices and population sizes of bacteria and fungi in the T6 treatment were the highest. The Chao1, observed species and Shannon indices of bacteria were 22.51%, 23.56% and 5.61% greater, respectively, than those of T4 (CK). The Chao1, observed species, Shannon and Simpson indices of fungi were 41.28%, 41.83%, 128.02% and 88.65% higher, respectively, than those of T4 (CK). At the genus level, the bacterial community compositions of T2 and T6 were the most similar, and the fungal community compositions of T1 and T5 were the most similar. Analysis of the genera in the dominant communities revealed that the application of microbial agents after dazomet fumigation increased the numbers and recovery rates of soil bacteria and fungi, especially the beneficial fungal genera, Lecanicillium, Cladosporium, Saccharomyces and Aspergillus. An investigation of strawberry growth and yield-related indicators revealed that the T6 treatment resulted in the lowest seedling mortality and the highest yield. In summary, adding microbial agents to soil with continuous cropping of strawberry after fumigation with dazomet is a scientifically sound and effective method for reconstructing the balance of the soil microbial flora and overcoming the obstacles associated with continuous cropping. In this study, the T6 (actinomycetes) treatment presented the best performance.